Pulverizing medication as a harm reduction and intentional drug overdose prevention strategy: Two case studies. Issue 3 (24th June 2021) - Takanobu, Keisuke; Okazaki, Daisuke; Watanabe, Shinya; Mitsui, Nobuyuki; Tanaka, Teruaki
Abstract: Aims: We explored the use of pulverized medication as a new method to prevent intentional drug overdose. Methods: This case study presents data obtained from the medical records of two female patients, aged 19 and 27 years, who presented with schizophrenia and neurodevelopmental disorder, respectively. Both patients provided written informed consent. Medication was administered to the two patients in powdered form, as opposed to in tablet form, in an attempt to prevent intentional drug overdose. Results: This administration method successfully prevented intentional drug overdose for 3 and 5 years in each case, respectively. However, case‐control or prospective cohort studies are needed to rule out biases, including cognitive bias. Conclusion: Pulverizing medication is a simple and effective means of preventing intentional drug overdose by restricting access to the means of suicide, regardless of the type of mental disorder. Abstract : This case study presents two female patients, who repeated intentional drug overdose. Medication was administered to the two patients in powdered form, as opposed to in tablet form, in an attempt to prevent intentional drug overdose.